The Role of Team Communication in Management Activities - Mohammad Daffa Nugraha; Rafli Putra Pratama Efendi (Integrative Perspectives of Social and Science Journal, 2026)
Effective team communication is essential for achieving successful management activities. This article examines how communication plays various important roles in team settings and how it directly influences key managerial tasks like planning, organizing, leading, and controlling. This paper explores how communication strategies influence management results, based on current research, and emphasizes the importance of establishing effective communication methods to meet organizational objectives. The main topics covered are how communication affects team unity, the way decisions are made, methods for resolving conflicts, and the effect on overall work efficiency.